Research on the Construction of Smart Campus in Vocational Colleges in the Era of Big Data - Sun, Lihong (Journal of Research in Vocational Education, 2025)
This paper discusses the construction of smart campus in higher vocational colleges in the era of big data. Under the background of the big data, analyzes the management of higher vocational colleges face the problem, and discusses its connotation and characteristics, and on how to optimize the construction and management, give full play to the supporting function of big data, building intelligent learning environment, optimize the teachers and students oriented management wisdom campus construction strategy and countermeasure, etc.